Training on the Utilization of Waste Woods from Used Containers as Clothes Hanger for Youth Organization (Karang Taruna) - Hendy Rosadi; Ariani Rachman (Comment: an International Journal of Community Development, 2019)
Waste wood from used containers has the potential to be utilized as a product that has economic value. As one of the efforts to provide new horizon of skills and knowledge about an alternative use of used wooden containers, the Product Design Study Program of the Faculty of Fine Arts and Design of Trisakti University held a Community Service program in the form of training in the use of waste wood from used containers into clothes hangers. Aside from being an alternative to reduce container wood waste. This activity was to empower the community in this case is Youth Organization of “Karang Taruna”, this program is carried out in Cawang Village, District of Kramat Jati, East Jakarta, with target communities of Karang Taruna in the region. Considering the educational background of the target community who have never studied matters related to design principles, it is necessary to be given understanding and knowledge of the basics of design. Thus, in processing this used container wood, the artistic side will also be taken into consideration. The experimental method was carried out in an effort to solve the problems related to the processing of waste wood from the container so that the final product was produced in the form of a clothes hanger that was functional with selling value.